Economic burden of influenza-associated hospitalizations and outpatient visits in Bangladesh during 2010 - Bhuiyan, Mejbah U.; Luby, Stephen P.; Alamgir, Nadia I.; Homaira, Nusrat; Mamun, Abdullah A.; Khan, Jahangir A. M.; Abedin, Jaynal; Sturm-Ramirez, Katharine; Gurley, Emily S.; Zaman, Rashid U.; Alamgir, ASM; Rahman, Mahmudur; et al. (© 2014 Blackwell Publishing Ltd., 2017)
This article was published in the Influenza and other Respiratory Viruses [© 2014 Blackwell Publishing Ltd.] and The Journal's website is at: http://onlinelibrary.wiley.com/doi/10.1111/irv.12254/abstract